Epigenetic Landscapes of Endometriosis: From Pathogenesis to Precision Medicine - Więcek, Alicja; Bezubik, Aleksandra; Kananovich, Veranika; Pietrzyk, Kacper; Pietrucha, Tadeusz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2024)
Endometriosis, a challenging gynecological disorder characterized by the ectopic presence of endometrial-like tissue, presents significant diagnostic and therapeutic hurdles due to its complex etiology and diverse clinical manifestations. Recent advancements in understanding its pathogenesis have underscored the pivotal role of epigenetic alterations, offering new insights into disease mechanisms and therapeutic targets. Epigenetic changes in endometrial cells significantly contribute to endometriosis pathogenesis, disrupting normal physiology and hormone responsiveness, particularly to progesterone. Dysregulation of histone modifications, DNA methylation, and non-coding RNA expression disrupts cellular homeostasis and promotes disease progression. Histone modifications, notably methylation and acetylation, influence chromatin structure and gene expression, affecting progesterone responsiveness and disease progression. Epigenetic regulators such as Cfp1 modulate progesterone receptor expression and downstream signalling pathways, presenting potential therapeutic targets. Non-coding RNAs, including miRNAs and lncRNAs, exert regulatory effects on gene expression and are implicated in endometriosis pathogenesis. Dysregulated expression disrupts cellular homeostasis and promotes disease progression. Biomarker studies have identified specific miRNAs and lncRNAs associated with endometriosis, offering avenues for non-invasive diagnosis and targeted therapies. siRNA-based therapies targeting key genes involved in endometriosis pathogenesis show promise as novel treatment modalities. By modulating gene expression and cellular functions, siRNA-based therapies offer a targeted approach to mitigate pathological processes. In this review, we summarize recent findings in the molecular mechanisms and regulatory pathways of endometriosis, offering valuable insights into pathology and therapeutic interventions. Future research efforts aimed at elucidating the complex interplay between epigenetic regulators and disease pathways hold promise for innovative diagnostic tools and targeted therapies.